The influence of user-perceived benefits on the acceptance of microlearning for librarians' training - Irene Shubi Isibika; Chang Zhu; Egbert De Smet; Albogast K. Musabila (Association for Learning Technology, 2023)
Microlearning has shifted professional training and development and its acceptance depends on perceived user benefits. This study examines the influence of user-perceived benefits on librarians' acceptance of the microlearning approach in selected universities in Tanzania. Using a questionnaire informed by the variables of the Technology Acceptance Model (TAM) model to collect data from a sample of 64 librarians, the results indicated that the perceived ease of use was found to play a more significant role in the acceptance of microlearning than perceived usefulness. However, the lack of in-person/physical interaction with peers during the training deterred the use of microlearning by the librarians. The positive influence of perceived usefulness and ease of use on the acceptance of microlearning strengthens the relevance of adopting microlearning as a didactic technology for librarians' training. The findings imply that proper implementation of microlearning as a training avenue is key due to the plenteous benefits it affords over the challenges.